Mitskite pretstavi za svetot na mrtvite vo tradicionalnata kultura na Makedoncite Mythical Presentations of the World of the Dead in the Traditional Culture in Macedonia - Risteski, Ljupčo S. (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The author discusses the mythical presentations about the existence of two autonomous, different and opposing realities - this world and that world - the first of which is always marked as “ours” and human, and the second one as a strange and a distant world of demoniac creatures.